Digest: Incomplete convergence drives form–function relationship in gliders. (13th November 2020) - Quinn, Brooke L.
Abstract: Little is known about the presence of incomplete convergence in the evolution of vertebrate taxa, as it is difficult to differentiate between evolutionary methods responsible for the appearance of similar forms. Grossnickle et al. present the first study of convergence evaluating all six extant glider clades using phylogenetic comparative methods. The authors find that the unique skeletal morphology of extant glider species (i.e., longer and thinner limbs) results from incomplete convergence under Brownian motion.